Contribuição ao estudo dos concretos compostos com agregados graúdos de construção e demolição e cinza volante, em diferentes teores de substituição - Silva, Sérgio Roberto da (2017)
Nowadays, searching for alternatives materials for the construction industry has become imperative. Construction and demolition waste (CDW) and by-products from the thermoelectric industries, such as fly ash, are the subject of studies in several segments of the construction industry. Their use can be one of many significant efforts to achieve a more sustainable construction. This paper studies the influence of the interactions and incorporations of CDW and fly ash on the concrete properties. X-ray diffraction (XRD), X-ray Fluorescence Spectrometry (XRF) and particle size distribution analysis were used to characterize the investigated materials. The mechanical properties (compressive strength and splitting strength) and durability (water absorption and carbonation depth) of concrete with different CDW contents (25%, 50%, 75%, and 100%) were investigated as a coarse aggregate (10%, 15%, 25% and 30%) replacing Portland cement in different water/binder ratios (0.40, 0.45, 0.50, 0, 55 and 0.65). Based on the results, it was observed that the addition of fly ash replacing the Portland cement in concretes with CDW causes a reduction in mechanical properties and durability of concretes in the early ages. However, as the fly ash content increases in concretes with CDW there is an increase in the compressive strength ratio (fc91/fc28), and as the time of exposure to CO2 advances the carbonation coefficient tends to decrease.